ANALISIS MATERI PERAN WALISANGA DI INDONESIA DALAM BUKU SEJARAH KEBUDAYAAN ISLAM KELAS XII MADRASAH ALIYAH - Cahya, Alviani Indra Dwi; Miftah, Muhammad; Haryono, Fido Teguh (IAIN Bone, 2023)
Material analysis in textbooks needs to be done to provide input as revision material for books that are published later and become a consideration for teachers so that in carrying out learning to be more creative and innovative. Therefore, the authors conducted research on the feasibility analysis of Walisanga's role in Indonesia in the Islamic Cultural History textbook published by the Ministry of Religion in 2020. This research includes qualitative research with a literature study method. The results of the study show that the material for Walisanga's role in Indonesia is in accordance with core competencies, basic competencies, and learning objectives. Presentation of material and language feasibility is good. As well as the material is in accordance with the development of Madrasah Aliyah students. However, weaknesses were found, namely the material was felt to be incomplete, the lack of illustrations as supporting aspects of the presentation and there were several writings that were not in accordance with the correct Indonesian language rules. So that the material on Walisanga's role in Indonesia in this book needs to be improved. Quality subject matter will support the achievement of optimal learning objectives.